Low Power RF Test of a Quadrupole-free X-Band Mode Launcher for High Brightness Applications. (November 2019) - Torrisi, G.; Sorbello, G.; Celona, L.; Leonardi, O.; Mauro, G.; Gammino, S.; Castorina, G.; Spataro, Bruno; Faillace, L.; Dolgashev, V.
Abstract: In this work we present the low power RF characterization of a novel TM01 X-band mode launcher for the new generation of high brightness RF photo-injectors. The proposed mode launcher exploits a fourfold symmetry which minimizes both the dipole and the quadrupole fields in order to mitigate the emittance growth in the early stages of the acceleration process. Two identical aluminum mode launchers have been assembled and measured in back-to-back configurations for three different central waveguide lengths. From the back-to-back results we infer the performance of each mode launcher. The low power RF test, performed at the Istituto Nazionale di Fisica Nucleare Laboratori Nazionali del Sud (INFN-LNS), validate both the numerical simulations and the quality of fabrication. An oxygen-free high-conductivity copper version of the device is being manufactured for high power and ultra high vacuum tests that are planned to be conducted at SLAC.